A hazard-based approach to modelling the effects of online shopping on intershopping duration - Suel,E; Daina,N; Polak,JW (Transportation, 2017)
Despite growing prevalence of online shopping, its impacts on mobility are poorlyunderstood. This partially results from the lack of sufficiently detailed data. In thispaper we address this gap using consumer panel data, a new dataset for this context.We analyse one year long longitudinal grocery shopping purchase data from Londonshoppers to investigate the effects of online shopping on overall shopping activity pat-terns and personal trips. We characterise the temporal structure of shopping demandby means of the duration between shopping episodes using hazard-based durationmodels. These models have been used to study inter-shopping spells for traditionalshopping in the literature, however effects of online shopping were not considered.Here, we differentiate between shopping events and shopping trips. The former refersto all types of shopping activity including both online and in-store, while the latteris restricted to physical shopping trips. Separate models were estimated for each andresults suggest potential substitution effects between online and in-store in the contextof grocery shopping. We find that having shopped online since the last shopping tripsignificantly reduces the likelihood of a physical shopping trip. We do not observethe same effect for inter-event durations. Hence, shopping online does not have a sig-nificant effect on overall shopping activity frequency, yet affects shopping trip rates.This is a key finding and suggests potential substitution between online shopping andphysical trips to the store. Additional insights on which factors, including basket sizeand demographics, affect inter-shopping durations are also drawn.